2016
DOI: 10.1118/1.4955928
|View full text |Cite
|
Sign up to set email alerts
|

SU‐F‐J‐20: Commissioning and Acceptance Testing of the C‐Rad CatalystHD Surface Imaging System

Abstract: Introduction: With the increasing use of surface‐based, nonionizing image‐guided radiotherapy (IGRT) systems, a comprehensive set of clinical acceptance and commissioning procedures are needed to ensure correct functionality and proper clinical integration. Although TG‐147 provides a specific set of parameters, measurement methodologies have yet to be described. The aim of this study was to provide a comprehensive overview of the commissioning and acceptance analysis performed for the C‐Rad CatalystHD imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The average thermal drift of cameras was observed to be 0.12 mm in this study, which is similar to those reported by Shi et al [19]. However, Stanley et al [32] reported a higher thermal drift of 1 mm and a longer preheat time to reach stability. This may be due to the performance discrepancy of various cameras.…”
Section: Discussionsupporting
confidence: 90%
“…The average thermal drift of cameras was observed to be 0.12 mm in this study, which is similar to those reported by Shi et al [19]. However, Stanley et al [32] reported a higher thermal drift of 1 mm and a longer preheat time to reach stability. This may be due to the performance discrepancy of various cameras.…”
Section: Discussionsupporting
confidence: 90%
“…Once positioned, the daily QA phantom is imaged, and the agreement between the laser isocenter and surface imaging isocenter is quantified. Tolerances and stability have been previously reported by Stanley et al . Our current surface imaging daily QA tests include the laser accuracy, functionality of the system, and calculation of translational shifts (tolerance ±1 mm).…”
Section: Discussionmentioning
confidence: 73%
“…Drift is generally assessed as part of system commissioning [3] . Limited results have been reported related to the drift of thermal cameras for SGRT [4] , [5] and other [6] patient monitoring systems. Conceptually simple to measure [7] , the implications of drift on clinical procedures are more complex and have not been described in the literature.…”
Section: Introductionmentioning
confidence: 99%